A power-saving scrolling scheme for browsers on mobile OLED systems. (23rd September 2021) - Chang, Hao-Chun; Yang, Yu-Chieh; Yu, Liang-Yan; Ho, Yao-Hua; Lin, Chun-Han
Browsers are critical mobile applications, and their power consumption plays an important role in mobile systems. This paper studies ways of reducing the power consumption of OLED displays when users use scrolling operations in browsers without reducing the quality of the user experience. The proposed power-saving scrolling scheme links the visual appeal of web pages and the power models of OLED displays. To judge the visual appeal, a content-based analysis is presented. Then, power-saving transformation programs are generated by two algorithms. Next, a scrolling monitor is designed to activate the transformation during scrolling operations. To provide a better user experience, two mechanisms are also proposed to smooth the transformation process and to improve the analysis efficiency. Finally, real-world web pages are used to evaluate the performance on a commercial smartphone. The results of comprehensive experiments show that the proposed scheme can achieve OLED power savings in the range 16-30%.